1975
DOI: 10.1002/eji.1830050411
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific acid esterase activity: A criterion for differentation of T and B lymphocytes in mouse lymph nodes

Abstract: A modified technique was used to demonstrate lymphocytic acid alpha-naphthyl acetate esterase activity in frozen sections of mouse lymphoid tissue or smears. Positive, dot-like reaction products were noticed in more than 94% of the lymphocytes located in the diffuse cortical ("paracortical", "thymus-dependent") area of mesenteric lymph nodes of young adult ICR mice. Almost identical values were found for lymphocytes in the cisterna chyli. In contrast, the follicular cortex which is predominantly occupied by B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
12

Year Published

1977
1977
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(127 citation statements)
references
References 16 publications
5
110
0
12
Order By: Relevance
“…Frozen sections from normal and rheumatoid synovial tissue and cytocentrifuge preparations of cells obtained from normal and rheumatoid synovial specimens were investigated for the presence of acid alpha-naphtyl acetate esterase (ANAE) (22), naphthol AS-D acetate esterase (NASDAE), inhibitable by sodium fluoride (NaF) (23,24), and naphthol AS-D chloroacetate esterase (NASDCAE) (25). ATPase staining was performed on normal suspended synoviocytes (26).…”
Section: Sources Of Tissuementioning
confidence: 99%
“…Frozen sections from normal and rheumatoid synovial tissue and cytocentrifuge preparations of cells obtained from normal and rheumatoid synovial specimens were investigated for the presence of acid alpha-naphtyl acetate esterase (ANAE) (22), naphthol AS-D acetate esterase (NASDAE), inhibitable by sodium fluoride (NaF) (23,24), and naphthol AS-D chloroacetate esterase (NASDCAE) (25). ATPase staining was performed on normal suspended synoviocytes (26).…”
Section: Sources Of Tissuementioning
confidence: 99%
“…The first is a different differentiation of lysosomes, as an intracellular organelle, in T and non-T lymphocytes, reflecting their cellular functions. Mueller et al [7] reported that the cytochemical activity might be acquired by T lymphocytes just before, during/or shortly after peripheralization. Horwiz et al ]8] noted that a single intense reaction by acid esterase staining, which is characteristic in T lymphocytes, disappears after mitogen-induced transformation.…”
Section: 2mentioning
confidence: 99%
“…The alpha naphtyl acetate esterase (ANAE) staining method is one of these tests, along with the enzymehistochemical analysis method, which provides different reactions to each of the blood cells (Mueller et al 1975;Higgy et al 1977;Basso et al 1980;Çelik et al 1994;Aştı et al 1996). It was determined that this lysosomal enzyme, which is a nonspecific esterase, is responsible for phagocytic and cytotoxic activities (Mueller et al 1975;Catowsky 1991). The image that is evaluated as positive in the leukocytes stained with the ANAE method is a homogeneous reaction of brown-red granules under the cell membrane or in cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…The image that is evaluated as positive in the leukocytes stained with the ANAE method is a homogeneous reaction of brown-red granules under the cell membrane or in cytoplasm. This enzyme is generally stained with 1-5 granules in lymphocytes (Ozcan 2005;Karaca et al 2006;Şimşek et al 2009), with dense homogeneous granules in monocytes (Mueller et al 1975;Higgy et al 1977;Basso et al 1980;Ramos et al 1992), and with granulocytes, it is stained in different granular styles, which vary according to the positivity or negativity of the animal species. In this method, neutrophil granulocytes show a negative reaction in humans (Higgy et al 1977), dogs, cats and horses (Aştı et al 1996), and they show a positive reaction in rats, cattle (Aştı et al 1996), sheep and goats (Osbaldiston & Sullivan 1978).…”
Section: Introductionmentioning
confidence: 99%